Produtividade e qualidade fisiológica de sementes de soja na região de Pelotas-RS - Trzeciak, Mário Borges (2009)
The soybean is the main Brazilian agricultural commodity, which is the second biggest worldwide productor of this culture, being one of the cultures that present better improvement in cultivated area at the Brazilian agro-industrial segment. Its expansion and establishment of agriculture border was only possible by the development of high productivity and width adaptation cultivars in different conditions of soil and weather. The soybean seeds are highlighted because of its morphologic and chemical features, by its high sensibility of the environmental factors. By getting a high productivity, it is necessary to use adaptative cultivars. On this way, it was noticed as a possible alternative the introduction of soybean cultivar grown in other Brazilian regions. Thus, this work aimed to identify cultivars with adaptation capacity in the region of Pelotas-RS, latitude 31o45 south, and whose productivity potential were high and whose seed were of high physiological quality. In order to increase the amount of seed use and, consequently, the technologies development for the region. The work was made at Embrapa Clima Temperado Estação Terras Baixas, at COODETEC company and at Agronomy Faculty Eliseu Maciel . There were used 25 cultivars of soybean, with and without the RR Technology from different groups of maturation. The sowing was made in December of 2007, being evaluated in cycle, number of snap beans and its productivity. The seeds were evaluated through germination tests, first counting of germination, accelerated aging, velocity emerging index and emerging in field. There were also determined the protein and oil contents. The cultivars CD 215, M Soy 6101, CD 217, CD 214 RR e CD 202 are recommended to the region of Pelotas RS, in order to obtain high productivity and high physiological quality of soybean seeds. It can be inferred from the gotten results that the soybean production with productivity between 2300 and 2700 is possible in the region of Pelotas RS. The soybean seed acquisition of high physiological quality is possible in the region of Pelotas RS. The soybean cultivars don t present coincidence among high protein and oil content, high productivity and high physiological quality of soybean seeds.